Inside the campaign finance battle : court testimony on the new reforms - Corrado, Anthony, 1957-; Potter, Trevor; Mann, Thomas E. (Brookings Institution Press, 2003)
The work examines the legal challenge to the new Bipartisan Campaign Finance Reform Act (BCRA) which is in federal court. It contains edited selections of reports filed by scholars and practitioners on both sides of the legal debate over the new campaign finance law.